Selective and reversible self-assembly of C60 fullerene on a 9, 10-bis(S-acetylthiomethyl)anthracene modified gold surface. Issue 58 (31st May 2016) - Piotrowski, P.; Pawłowska, J.; Bilewicz, R.; Kaim, A.
Abstract : Synthesized di- S -acetyl anthracene derivative deposited on gold surface allows for selective multi-cycle capture of C60 fullerene by reversible forming well-ordered monolayers of C60 fullerene–anthracene adduct according to Diels–Alder reaction. Abstract : A tailored di- S -acetyl anthracene derivative was synthesized and anchored to a gold electrode in order to produce well-ordered monolayers of C60 fullerene according to the Diels–Alder reaction. AFM studies, IRRAS and XPS spectroscopy proved successful grafting onto the Au surface of both anthracene dithioacetate and its subsequent Diels–Alder adduct with C60 fullerene. Electrochemical properties of the fullerene adduct monolayers were characterized by cyclic voltammetry. Voltammetry was used also to prove the thermally controlled release of C60 fullerene from the Diels–Alder adduct modified gold surface. Selective affinity of the anthracene derivative deposited on gold towards the C60 molecule allows for the recognition and separation of C60 from the fullerene soot.